APRESIASI DAN KREASI SENI RUPA NUSANTARA SEBAGAI PENDORONG KECINTAAN TERHADAP BUDAYA NUSANTARA BAGI SISWA SEKOLAH INDONESIA RIYADH ARAB SAUDI - Ponimin, Ponimin (Studi Budaya Nusantara, 2023)
A sense of love, belonging and pride in the culture of the Nusantara must still be grown in every Indonesian citizen. This is to strengthen their identity as a Nusantara nation so as not to be uprooted from their cultural roots. This is also no exception for the students of the Riyadh Indonesian School (SIR) in Saudi Arabia. The strategies to encourage this sense of love, belonging and pride include art appreciation activities and art creations for the Nusantara's cultural arts to them in a way that is implemented in the overseas community service program from LPPM State University of Malang. To achieve the results of these activities such as workshops and training methods are applied which include the following methods: (1) The presentation with the theme of fostering insight to SIR students (Sekolah Indonesia Riyadh), (2) The Demonstration method for creating Nusantara fine arts, (3) Discussion and evaluation of the results of activities and implementation of activities, (4) Analysis of the results of appreciation activities and creations of Nusantara fine arts that have been carried out by students as program targets. The results of this activity are expected that the students will have an understanding of the importance of loving through the act of appreciation and creation of Nusantara cultural arts as Indonesians. On the other hand, the students have the ability and technical experience in creating, especially in the field of Nusantara fine arts which is achieved through training activities to create fine arts.